63.1k views
5 votes
Complete the equivalent equation for -7x-60=x^2+10x (x+ )(x+ )=0

1 Answer

5 votes
we have that
-7x-60=x²+10x
x²+10x+7x=-60
x²+17x=-60
(x²+17x+8.5²)=-60+8.5²
(x+8.5)²=12.25
(+/-)(x+8.5)=√12.25--------> (+/-)(x+8.5)=3.5
(+)(x+8.5)=3.5------> x=-5
(-)(x+8.5)=3.5------> x=-12

therefore
(x+5)*(x+12) is equivalent to -------> -7x-60=x²+10x

the answer is
(x+5)*(x+12)

User Martin Odhelius
by
5.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.